Combined Spermacoce radiata and Hypselodelphys poggeana Extract (CESH) Protect against Oxidative Stress and Enhances Haematological Parameters in Benign Prostatic Hyperplasia-induced Rats - Robert Ikechukwu Uroko; Favour Matthew Awah; Chinedu Aguwamba; Mercylyn Ezinne Uche; Ikenna Obiwuru; Chinomso Friday Aaron; Ezichi Favour Ofoezie (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
This study investigated the therapeutic effect of a combined extract of Spermacoce radiata and Hypselodelphys poggeana (CESH) on oxidative markers and haematological parameters in benign prostatic hyperplasia (BPH) induced rats. The study adopted five groups containing equal numbers of rats (n = 6), including normal control, BPH control, Finasteride control, BPH-induced rats treated with 200 mg/kg CESH, and BPH-induced rats treated with 600 mg/kg CESH. The rats were induced BPH by the subcutaneous administration of a 5 mg/kg testosterone propionate injection. At the same time, treatment finasteride and CESH to the respective groups were given orally 60 minutes after the BPH induction for 28 uninterrupted days. The induction of BPH with testosterone propionate injection caused a significant reduction in the serum levels of haematological parameters, including haemoglobin (Hb), packed cell volume (PCV), red blood cells (RBC), and platelet counts of the BPH control compared with normal control. The glutathione (GSH) concentration, glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione S-transferase, and catalase activities decreased significantly in the BPH control relative to the normal control. The BPH control had elevated white blood cell (WBC), and malondialdehyde (MDA) concentrations contrary to the high WBC and MDA in the normal control and CESH treated BPH induced rats, respectively. Conversely, the Hb, PCV, platelet count, GPx, SOD, catalase, GST, and GSH increased significantly in the finasteride and CESH-treated BPH-induced rats, respectively, compared to the BPH control. These findings show that CESH attenuates adverse effects of BPH on antioxidant parameters and oxidative markers, which may prevent BPH progression.